Adsorption Treatment Of Pulau Burung Sanitary Landfill Leachate Using Zeolite - Akma, Nur Farahiza (Universiti Sains Malaysia, 2022)
The majority of landfill leachates in Malaysia are high in ammonium nitrogen, which hinders biological treatment processes and harms rivers. Landfill leachates are described as the contaminated liquid that emerges from water percolating through a landfill. Leachate produced by a landfill for municipal solid waste (MSW) has a substantial impact on both surface water and groundwater. Therefore, in order to protect the environment, it is crucial to treat landfill leachate. This study investigates the composition of leachate from the Pulau Burung Sanitary Landfill (PBSL). In a lab experiment, zeolite was used to remove specific chemical components from the leachate, including COD, suspended particles, zinc, and turbidity. This was done to evaluate the efficiency of the adsorption treatment. According to the data of the study's adsorption experiments, the dosage of 1.0 g of zeolite at a pH 4 provided the optimal operating conditions for removing COD to the point where it satisfies the legal requirements for discharge throughout the entire system of municipal sewage. The COD elimination efficiency was at a 43.0 %. In the meantime, in terms of the turbidity, the optimum of zeolite to utilize in order to remove it up to 61.26 percent was 3g when the pH was 12. Hence, the conclusion that the adsorption technique used by the zeolite to treat the leachate was successful in these batch studies.